Perceptions and practices of pharmaceutical wholesalers surrounding counterfeit medicines in a developing country: a baseline survey - Khan Mohiuddin H; Akazawa Manabu; Dararath Eav; Kiet Heng B; Sovannarith Tey; Nivanna Nam; Yoshida Naoko; Kimura Kazuko (BMC, 2011)
Abstract Background Recent investigations by the Ministry of Health of Cambodia suggest that counterfeit medicines have been introduced into the pharmaceutical market in tampered packaging. To further explore this possibility, an interview survey was conducted at the wholesaler level to investigate the medicinal supply chain in Cambodia. Methods Managing executives of 62 (83.8%) registered wholesalers of modern medicines in Cambodia were interviewed in 2009 on their knowledge of, perception on, and practices related to counterfeiting issues through a semi-structured questionnaire. Results According to our findings, 12.9% of the wholesalers had encountered counterfeit medicine. However, they demonstrated a variety of perceptions regarding this issue. A majority (59.7%) defined counterfeit medicines as medicines without registration, while other definitions included medicines that were fraudulently manufactured, medicines without a batch/lot number, those containing harmful ingredients or a reduced amount of active ingredients, and expired medicines. Additionally, 8.1% responded that they did not know what counterfeit medicines were. During procurement, 66.1% of the wholesalers consider whether the product is registered in Cambodia, while 64.5% consider the credibility and quality of the products and 61.3% consider the reputation of the manufacturers. When receiving a consignment, 80.6% of wholesalers check the intactness of medicines, 72.6% check the specification and amount of medicines, 71% check Cambodian registration, 56.5% check that the packaging is intact, 54.8% check batch and lot numbers, 48.4% check the dates of manufacture and expiration, and 9.7% check analytical certificates. Out of 62 wholesalers, 14.5% had received medicines that arrived without packages or were separated from their packaging and had to be repacked before distribution. Significant statistical association was found between wholesalers who received medicines separately from their packs/containers and who consider their belief on reliability of pharmaceutical products of certain manufacturing country during procurement (Chi-square: 12.951, P = 0.002). When wholesalers divide medicines from larger packs into smaller ones, 54.8% use packaging purchased from local markets. Conclusion A number of wholesalers think counterfeit medicines are medicines without registration, and/or do not have any uniform ideas on the issue and what to do, when they find or suspect counterfeits. Furthermore, their strict adherence to anti-counterfeiting measures is urgently needed.